Perancangan E-Commerce Sebagai Media Pemasaran Kerajian Bambu - F. Lia Dwi Cahyanti; Fajar Sarasati; Widiastuti Widiastuti; Elly Firasari (Universitas Hamzanwadi, 2021)
At this time progress economic in Indonesia is very rapidly, This is evidenced by the emergence of many newly pioneered business fields one of which is a company engaged in marketing. Each Company makes various efforts to keep the company be growing. UKM Kerajinan Bambu Brajan in Sleman Yogyakarta has a problem's promotion activities and product sales that are still traditional and manual. The purpose of this study is to design e-commerce as a traffic bamboo handicrafts on UKM in Brajan village. With the creation of the e-commerce website as the marketing of products is expected to help traffic the product so that it can be widely known to the public. The waterfall model is what is used to design this product in systematic steps. This study produces a ecommerce website that has been tested for its feasibility using the black box testing method. This Website provides information to consumers about the products in UKM Kerajinan Bambu Brajan, as well as provides a facility of the UKM in the process of selling and marketing products.